DIFFERENCES OF LANGUAGE LEARNING STRATEGIES IN ENGLISH AS A SECOND LANGUAGE CLASSROOM OF SOCIAL COLLAGE STUDENTS - Asti Gumartifa; Indah Windra Dwie Agustiani; Febri Aditiya (STKIP Persada Khatulistiwa Sintang, 2020)
Most of the Indonesian students depend on the teachers in learning English. University students do not understand the language learning strategies properly. The purpose of this research is to investigate language learning strategies used by social collage students. The participants were 125 students of economy faculty at the University of Muhammadiyah Palembang. The tool used was a questionnaire of SILL. The data collected were analyzed statistically. The results showed that students were indeed using metacognitive (M=4.11), memory (M=3.88), social (M=3.81), cognitive (M=3.66), affective (M=3.62), and compensation strategies (M=3.49). While both males and females used metacognitve strategies with the statistically (M=4.15) for females and (M=4.05) for males. Metacognitive reading strategy is the dominant used by the students. Metacognitive strategies have a strong and important impact on effective students learning English as a second language. Besides, students integrate both direct and indirect learning strategies. This brings an additional field of research to demonstrate the construction of LLS guidance on the gender and level of students’ education.